Power, discourse, and student agency in colonial education - Tesfaye Woubshet Ayele (Educare)
This paper aims to glean valuable insights from critical pedagogy in order to apply them to the field of African literary studies. Specifically, I am interested in how approaches inspired by culturally responsive education can help us revisit the important but under-researched topic of student agency as it features in fictional works that deal with colonial education in Africa. Although colonial education in literature has been the subject of intense focus in postcolonial theory, such theorizations largely examine how colonial education reproduces colonial rule through the dissemination of colonial discourse/ideology. When student agency in the colonial education systems is addressed, conventional postcolonial theory sees it as being overwhelmed or assimilated by colonial discourse and power. Ideas emanating from critical pedagogy and culturally responsive education are of value here in that they can elucidate how students interact with and even resist the pedagogical and political power of the colonial education system. Ngũgĩ wa Thiong’o’s novel Weep Not, Child is an illustrative example of how such a critical-pedagogy-inspired approach can help us reorient literary studies of colonial education systems.